Strategic uses of vague expressions in Indonesian political talk show Mata Najwa: A pragmatic discourse analysis - Sri Handayani; Prapti Wigati Purwaningrum (NOTION: Journal of Linguistics, Literature, and Culture, 2026)
The use of vague expressions in political discourse interaction is often viewed as a form of linguistic ambiguity, however, previous research has not adequately explained their strategic function in confrontational public interactions, especially in the in the context of political talk shows. This study aims to examine the pragmatic function of vague expressions as a communication strategy in the Mata Najwa talk show episode "Berebut Tahta di Tengah Wabah" (Fighting for the Throne in the Midst of an Outbreak).  A descriptive qualitative approach is implemented.  In order to get in depth data analysis, pragmatic discourse analysis based on operational linguistic indicators, including indefinite quantifiers, hedging devices, general extenders, and placeholder expressions is used. The data consists of 127 responses from nine resource persons to host questions and statements, with a tendency to use vague expressions in sensitive questions. The results show that vague expressions function as a discursive strategy structured in three main forms. First, a mitigation strategy encompasses self-protection, politeness, and information limitation to reduce epistemic commitment and avoid sensitive issues. Second, an affirmative strategy utilizes factual data and assertive statements to build credibility and public trust. Third, a conversation management strategy utilizes inclusive pronouns and cultural symbols to build legitimacy and manage power relations. This finding confirms that vagueness is a strategic pragmatic practice in political communication that plays a role in shaping public perception and legitimacy.